Design and Implementation of Low Power, Area Crosstalk Reduction Using Static Timing Analysis - Obulesu, Battari; Ashok, P.; Rajesh, J.; Madhu, K.; Rakesh, G.; Raghava Sarath Chandra Reddy, Guddety (E3S web of conferences, 2024)
One of the biggest issues with VLSI connections is crosstalk, which is caused by coupling capacitance. Crosstalk reduces operation performance during switching activities and produces undesired output. Noise level rises as switching frequency does as well. Crosstalk will be eliminated by encode the data before connecting into the bus line. This procedure reduces the crosstalk issue by using the improved logic architecture. The proposed approach utilizes a combination of circuit-level optimization techniques, such as gate sizing and interconnect optimization, and advanced timing analysis tools to minimize power consumption and reduce crosstalk.